2005
DOI: 10.1002/mop.21328
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of spurious radiations of patch antennas using split‐ring resonators (SRRs)

Abstract: The spurious radiation of patch antennas is suppressed by the band‐stop characteristic of split‐ring resonators (SRRs). The SRRs are located near the feed line of the upper substrate so as to couple the perpendicular magnetic field to the SRRs. The SRRs can be characterized with negative permeability and positive permittivity around the resonance frequency and, thus, waves cannot propagate. To eliminate the first and second spurious radiations, the design equations of a band‐stop filter using SRRs are suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…CRLH contains two RH and LH parts . Different model of parasitic element are used in antenna such as U‐shaped parasitic elements or split ring resonator (SRR) element . Negative index metamaterial are known as composite materials that show negative effective permittivity and negative effective permeability and in those, material negative permeability was obtaining by structure such as SRRs, spiral resonators, and V‐shaped resonators .…”
Section: Introductionmentioning
confidence: 99%
“…CRLH contains two RH and LH parts . Different model of parasitic element are used in antenna such as U‐shaped parasitic elements or split ring resonator (SRR) element . Negative index metamaterial are known as composite materials that show negative effective permittivity and negative effective permeability and in those, material negative permeability was obtaining by structure such as SRRs, spiral resonators, and V‐shaped resonators .…”
Section: Introductionmentioning
confidence: 99%
“…is computed using formula given in equation (7) and other different network parameter should satisfy the following equations (7)(8)(9)(10).…”
Section: ) J-k Inverter Designmentioning
confidence: 99%
“…impedance matching, gain, efficiency, directivity, front-to-back ratio etc. [9][10]. Along these features SRR are used to improve the broad banding; and suppressing the sideband and mutual coupling between two radiators [10][11].…”
Section: ) J-k Inverter Designmentioning
confidence: 99%
“…A thorough study of different metamaterials and their characteristics has been reported widely [3][4][5][6] over the last years. The key applications of metamaterials mainly exploited are antenna miniaturization, bandwidth enhancement, directivity/gain enhancement, spurious radiation suppression [7][8][9], etc. The researchers are very fond of making new artificial materials to keep enhancing the performance of wireless communication systems.…”
Section: Introductionmentioning
confidence: 99%